Nematodes as biocontrol agents - Grewal, P. S.; Ehlers, R. U.; Ehlers, R. U.; Grewal, P. S.; Shapiro-Ilan, D. I.; Shapiro-Ilan, D. I. (Wallingford :CABI Publishing, 2005)
This book documents and illustrates the major developments in the use of nematodes for biological control of insects and slugs. It has seven parts covering the morphology and taxonomy of all nematode groups used as biological control agents; entomopathogenic nematodes; entomophilic nematodes; slug-parasitic nematodes; predatory nematodes; fungal-feeding nematodes; and critical issues and research needs for future expansion of nematode use in biological control. Nematode biology, commercial production, formulation and quality control, application technology, strategy and safety are discussed. Separate chapters are devoted to the application of nematodes in different cropping systems and the efficacy of nematodes against specific pests such as plant parasitic nematodes and fungal pathogens.
Keywords: FF610 - Viral, Bacterial and Fungal Diseases of Plants, (New March 2000); FF620 - Plant Pests, (New March 2000); HH100 - Biological Control; LL030 - Other Invertebrate Culture (Not Aquaculture); YY100 - Anatomy and Morphology (Wild Animals), (New March 2000); YY200 - Reproduction, Development and Life Cycle (Wild Animals), (New March 2000); YY700 - Pathogens, Parasites and Infectious Diseases (Wild Animals), (New March 2000); ZZ380 - Taxonomy and Evolution